PENERAPAN KEBIJAKAN E-GOVERNMENT SISTEM APLIKASI E-KINERJA BERBASIS WEB DI LINGKUNGAN PEMERINTAH KABUPATEN MUKOMUKO - Alfathan Akbar Artha Ramadhan; Maulana Mukhlis; Pitojo Budiono (Journal Publicuho, 2023)
The purpose of this study is to find out how E-Government policy issues through the web-based E-performance application system in the Mukomuko Regency government environment. This research uses qualitative descriptive research and data collection through observation, interviews, and documentation, with the intention of being able to objectively describe facts and phenomena that are research problems. The results showed that the issue of E-Government policy through the implementation of a web-based E-performance application system in the Mukomuko Regency government environment has not been going well. This is because there are still shortcomings in the E-performance application system used and several inhibitory factors found. The limitations of research specifically only address e-government policy issues through the implementation of a web-based E-performance application system in mukomuko regency. This research can be used as a reference for innovation and policy development in the field of E-government through the concept of innovation adaptation.